Intra- and Extracellular Effector Vesicles From Human T And NK Cells: Same-Same, but Different? - Lettau, Marcus; Janssen, Ottmar (Frontiers in Immunology, 2021)
Cytotoxic T lymphocytes (CTL) and Natural Killer (NK) cells utilize an overlapping effector arsenal for the elimination of target cells. It was initially proposed that all cytotoxic effector proteins are stored in lysosome-related effector vesicles (LREV) termed “secretory lysosomes” as a common storage compartment and are only released into the immunological synapse formed between the effector and target cell. The analysis of enriched LREV, however, revealed an uneven distribution of individual effectors in morphologically distinct vesicular entities. Two major populations of LREV were distinguished based on their protein content and signal requirements for degranulation. Light vesicles carrying FasL and 15 kDa granulysin are released in a PKC-dependent and Ca2+-independent manner, whereas dense granules containing perforin, granzymes and 9 kDa granulysin require Ca2+-signaling as a hallmark of classical degranulation. Notably, both types of LREV do not only contain the mentioned cytolytic effectors, but also store and transport diverse other immunomodulatory proteins including MHC class I and II, costimulatory and adhesion molecules, enzymes (i.e. CD26/DPP4) or cytokines. Interestingly, the recent analyses of CTL- or NK cell-derived extracellular vesicles (EV) revealed the presence of a related mixture of proteins in microvesicles or exosomes that in fact resemble fingerprints of the cells of origin. This overlapping protein profile indicates a direct relation of intra- and extracellular vesicles. Since EV potentially also interact with cells at distant sites (apart from the IS), they might act as additional effector vesicles or intercellular communicators in a more systemic fashion.